Effect of fortification of commercial glycerol and crude glycerol to straw based mixed substrate on fermentation kinetics and energy value - Savitha, G; Lokesha, E; Suson, Thingujam; Sondur, S N; Srinivas, Bandla (Indian Journal of Dairy Science, 2019)
The study evaluated the effect of commercial grade pure glycerol (PG) and, crude glycerol (CG) which was obtained during biodiesel production on rumen fermentation kinetics in vitro. Glycerol purity of both the sources was 99.9% and confirmed with GC-MS. CG was little alkaline with 7.11 pH and consisted total tannins, alkaloids and flavonoids 24.09±3.21, 16.63±3.97 and 20.52±4.11µg/ml, respectively than PG. In vitro fermentation kinetics (IVFK) and substrate utilization by rumen microbes was studied by applying first order kinetics to in vitro gas production (IVGP) technique. Substrate having roughage to concentrate ratio of 60:40 was used without glycerol fortification (control) or fortified with10% PG or CG. Total gas production (TGP) was significantly (P<0.01) increased in PG or CG compared to control. Lag time in CG was more (P<0.05) than PG due to presence of impurities. Substrate IVDMD and IVNDFD were comparable between PG and CG. IVTVFA was significantly (P<0.01) increased in PG or CG than control. Metabolizable energy (ME) value of the substrate was improved by 27 and 32% respectively, in PG or CG compared to control. Study concluded that IVFK and substrate utilization between commercial or crude glycerol was comparable. Based on improved TVFA concentration and ME value, CG or PG could be fortified to dairy ration to enhance substrate fermentation and energy yield.